Effect of Turmeric Rhizome Powder on the Activity of Some Blood Enzymes in Broiler Chickens - Emadi, M.; Kermanshahi, H. (International Journal of Poultry Science, 2006)
In order to study the effect of turmeric rhizome powder (TRP) on the activity of some blood enzymes in broiler chicken, a 49 days experiment using corn-soybean meal based diet containing four levels of TRP (0.0, 0.25, 0.50 and 0.75%) as treatments with five replicates in a completely randomized design was conducted. 200 Ross male broiler chicken from 0-49 days were housed in 20 pens and received feed and water ad-libitum. At 21 and 42 days of age, one blood serum sample from each replicate of treatment was collected. Inclusion of TRP significantly increased LDH and AST enzymes (P< 0.05). TRP in the diets also significantly decreased ALT and ALP enzymes (P< 0.05). Under the conditions of this study, it was concluded that TRP might have some positive effects on liver enzymes that directly or indirectly reflects a healthier liver status in broiler chickens.